2021
DOI: 10.1007/s00429-021-02312-w
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-parietal homotopy in resting-state functional connectivity predicts task-switching performance

Abstract: Homotopic functional connectivity reflects the degree of synchrony in spontaneous activity between homologous voxels in the two hemispheres. Previous studies have associated increased brain homotopy and decreased white matter integrity with performance decrements on different cognitive tasks across the life-span. Here, we correlated functional homotopy, both at the whole-brain level and specifically in fronto-parietal network nodes, with task-switching performance in young adults. Cue-to-target intervals (CTI:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 96 publications
2
9
0
Order By: Relevance
“…Homotopic interhemispheric rsFC of the occipital lobe has been found to be negatively associated with visual long-term memory performance in healthy children (6–10 years old; Gracia-Tabuenca et al ., 2018 ). In young adults, homotopic interhemispheric rsFC of the fronto-parietal network was positively correlated with task-switching performance (Vallesi et al ., 2022 ). Homotopic rsFC of the language network can also predict new language learning performance, although different regions correspond to different aspects of new language learning (Sander et al ., 2022 ).…”
Section: Vmhc Methodology and Functional Importance Of Homotopic Inte...mentioning
confidence: 99%
“…Homotopic interhemispheric rsFC of the occipital lobe has been found to be negatively associated with visual long-term memory performance in healthy children (6–10 years old; Gracia-Tabuenca et al ., 2018 ). In young adults, homotopic interhemispheric rsFC of the fronto-parietal network was positively correlated with task-switching performance (Vallesi et al ., 2022 ). Homotopic rsFC of the language network can also predict new language learning performance, although different regions correspond to different aspects of new language learning (Sander et al ., 2022 ).…”
Section: Vmhc Methodology and Functional Importance Of Homotopic Inte...mentioning
confidence: 99%
“…Overall, these studies reported a consistent vulnerability of the FPN, despite the clinical heterogeneity of EOAD sample (i.e., in these studies, EOAD patients were not characterized by their clinical phenotype). The FPN includes the lateral prefrontal cortex and temporoparietal regions and it has been linked with executive functions (Smith et al, 2009;Laird et al, 2011;Vallesi et al, 2021). The FPN also plays a critical role in coordinating behavior in an accurate and flexible goal-driven manner (Marek and Dosenbach, 2018).…”
Section: Functional Connectivity Studies In Early-onset Alzheimer's D...mentioning
confidence: 99%
“…Crucially, HC can be taken as an index of local interhemispheric integration (Jin et al 2020 ). Values of homotopic FC are higher than those of other forms of intra- and interhemispheric FC (Stark et al 2008 ), and it correlates with the performance of cognitive tasks, such as visuospatial attention (Gracia-Tabuenca et al 2018 ) and executive function (Zhao et al 2020 ; Vallesi et al 2021 ). Furthermore, altered patterns of homotopic FC were observed in a wide array of pathologic conditions or abnormal states (Shan et al 2021 ; Yu et al 2018 ; Chen et al 2016 ; Guo et al 2019 ; Deng et al 2021 ; Loomba et al 2021 ; Yao et al 2021 ; Li et al 2015 ; Zhao et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%